Development of E-Worksheet on Linear Equations and Inequalities Topics Based on Tri-N - Nisa Wijayanti; Tri Astuti Arigiyati; Fikri Aulia; Sri Adi Widodo (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2021)
The purpose of this study was to design e-worksheet mathematics on the subject of linear equations and inequalities based on Tri-N and to determine the validity of mathematics e-worksheet on the subject of linear equations and inequalities based on Tri-N. This research uses the stages of define, design, and development. The data collection technique used at the define stage is documentation and at the development, the stage is a validation sheet. The data analysis technique carried out at the define stage is qualitative descriptive analysis, at the design stage is descriptive analysis, and at the development, the stage is a quantitative descriptive analysis. The results showed that the e-worksheet mathematics subject of linear equations and inequalities based on Tri-N was valid with the tendency of the product to be in the medium category. This can be seen from the results of V-Aiken calculations obtained between 0.589 to 0.933. Based on these results it is suggested that the e-LKPD mathematics can be used in the dissemination stage. Keywords: e-worksheet, Tri-N, design, the validity of the product.